Diu - Shokoohy, Mehrdad. (Leiden ; Boston)
xi, 412 sayfa
Keywords: “The ex-Portuguese Island of Diu - a once strategic maritime gateway to the bay of Cambay, Gujarat, India - features in the corpus of Portuguese history and literature, but a comprehensive study of the island was lacking. Mehrdad and Natalie Shokoohy, known for surveying little-known historic sites in India, present the study of the built environment of Diu in conjunction with the contemporaneous Indian histories in Arabic and Persian, resulting in a fresh view of Indian Ocean commerce and conquest. Extensive surveys of the Fort, the Town and the Island, include the epigraphy, fortifications, urban fabric, mosques, shrines, churches, monasteries, water infrastructure and the Zoroastrian Fire Temple and Towers of Silence. Fragmentary Hindu and Jain archaeological remains are also noted“ --